Investigação de ações relativas à Construção Enxuta em construtoras goianas - SOUZA, Leiliane Santana (2010)
In response to the needs of the building market, the model for operational management of the Lean Construction arises taking as a basis to adopt methods that seek to generate added value to the product, without resulting in significant increase in costs, deadlines or loss of quality. The aim of this study is evidence demonstrating the use of the philosophy of lean construction in the city of Goiania. A multiple case study was conducted, in the sites of eight companies of the capital, showing the features service to four principles of lean construction worked in this research. They are: increasing the transparency of the process, reducing variability, increasing flexibility and output value of the product / service from the considerations of customers (external / internal). A check list was applied to the management team in order to identify the presence or absence of the principles described. Data was collected through direct observation and photographic record. The analysis of the reports shows that participating companies seeking to reach the longing of the principles of lean construction in a particular way, even if it is not done intentionally, since no use of such methodology as a form of management. The approach takes the principles studied mainly on reducing losses from the streamlining, flexibility and transparency of processes, customer expectations and something important to consider. The paper's secondary objective disclosure of the issue in this region, for this was prepared a booklet for employees in the building, containing practical examples for use in the work. The relevance as to approach the subject is made for the originality of this study. This is an unprecedented survey in the researched region are expected to conduct the study and dissemination of results motivate these firms to develop practices that are not performed in the workplace.